The competency of counsellors at diverse work settings in managing mental health issues in Malaysia - Rafidah, A.M.J. (2016)
Multicultural counselling literature and research have highlighted the need for practising counsellors around the globe to be multiculturally competent. However, in Malaysia, such competencies were not yet formulated for use. This shows that multicultural counselling is still in its developing stage in the practice and training of counsellors in Malaysia. Although multicultural counselling courses have been introduced and taught in the counsellor education programs in most Malaysian universities and colleges since the 1990s, there is no information regarding its effectiveness to enhance the practice of multicultural counselling among professional counsellors at diverse work settings in Malaysia. This paper explores relevant literature and research findings to discuss the status and extent of multicultural counselling competency of counsellors who are working at diverse work settings in Malaysia. The paper argues two things: (1) The need for counsellors to be multiculturally competent and incorporate these competencies in their counselling practice at diverse work settings, and (2) The need for counsellors to upgrade their mental health literacy from both etic and emic perspectives. The paper also discusses some examples of culturally sensitive issues that were considered as challenging cases by Malaysian counsellors during counselling sessions. The paper concludes by presenting some strategies and tips in enhancing counsellors' multicultural counselling competency in managing mental health issues at diverse work settings in Malaysia.